Answer: y= ln x will be the function which is represented in the graph.
Explanation: since, we know that a function must be satisfied its own point. And according to the graph function passes through the point (1,0) in the positive x-axis. so it must be satisfied the points.
for y=e^x, if x=1, y=e^1=e ≠ 0, thus it can not be y=e^x
for y=e^x-1, if x=1, y=e^1-1=e-1≠0 thus it can not be y=e^x-1
for y=ln x, if x=1, y=ln 1= 0 thus (1,0) is one of the point of function ln x.
for y= ln x-1, if x=1, y=ln1-1=0-1=-1≠0 thus it can not be y=lnx-1
Therefore, by the above explanation we can say that the point only satisfied for function lnx.
Thus, y=ln x will be the equation which is represented by the following graph.